Interface Molecular Functionalization of Cu2O for Synchronous Electrocatalytic Generation of Formate - Tan, Dongxing; Wulan, Bari; Ma, Jizhen; Cao, Xueying; Zhang, Jintao (Nano letters, 2022)
The electrocatalytic generation of valuable fuels and chemicals from carbon dioxide (CO2) and others with the assistance of clean solar energy is a highly promising way to realize the carbon-neutral cycle, which invokes the systematic development of advanced electrocatalysts for efficient and selective redox reactions of feedstocks. Herein, we demonstrate the interface modification of cuprous oxide with polyvinylpyrrolidone (PVP) to improve the electrocatalytic efficiency for the synchronous formate generation. Density functional theory calculations reveal that the interfacial properties can be effectively regulated by the PVP functionalization for the favorable formation of intermediates to improve the selectivity of formate generation. Importantly, the advanced electrocatalyts enable an efficient coupling of CO2 reduction with methanol oxidation in an electrochemical cell powered with a solar cell. The work provides a predictive link between the electrocatalytic redox reactions by applying the interfacial regulation strategies of electrocatalysts.